Pengaruh Indeks Pembangunan Manusia (IPM), Ketimpangan Pendapatan dan Tingkat Pengangguran Terhadap Kemiskinan di Provinsi Aceh - Mulyani, Ika; Ridha, Ahmad; Miswar, Miswar (Journal of Economics, Bussiness and Management Issues, 2024)
This study aims to analyze the effect of Human Development Index (HDI), Income Inequality, and Unemployment Rate on Poverty in Aceh Province both partially and simultaneously. The method of assistance used in this study is a quantitative method with the Eviews tool. The results of the study indicate that the Human Development Index variable (X1) has a coefficient of -2.953952 and a t count of -22.91131, which is greater than the t table of 1.967 and a probability value of 0.000 which is less than 0.05, so H1 is accepted. This shows that HDI has a negative effect on poverty in Aceh Province. For the Income Inequality variable (X2), the coefficients are 0.07867 with a t count of 1.988778 greater than the t table of 1.967 and a probability of 0.0478 which is less than 0.05, so H2 is accepted, which means that Income Inequality has a positive effect on poverty. Meanwhile, for the Unemployment Rate variable (X3), the coefficient is 0.002017 with a calculated t of 0.178943 smaller than the t table of 1.967 and a probability of 0.7444 which is greater than 0.05, so H3 is rejected, indicating that the Unemployment Rate does not have a significant effect on poverty. Simultaneously, the calculated F value of 218.5922 is greater than the F tab le of 2.633 with a probability value of 0.000000 which is smaller than 0.05, so H4 is accepted, which means that the Human Development Index, Income Inequality, and Unemployment Rate together have an effect on poverty in Aceh Province.